(2x - 4)^2
= (2x)^2 - 16x + 4^2
= 4x^2 - 16x + 16
2007-06-28 14:34:07
·
answer #1
·
answered by Kemmy 6
·
2⤊
0⤋
That is
(2x-4)(2x-4)
Use FOIL
First terms times first terms,
outer terms times outer terms
inner term times inner term, and
last term by last term
2x * 2x = 4x^2
2x * -4 = -8x
2x*-4 = -8x
-4 * -4 = 16
Then combine like terms.
2007-06-28 21:35:53
·
answer #2
·
answered by lilfry14 3
·
1⤊
0⤋
2x * 2x = 4x^2
2x * -4 = -8x
2x*-4 = -8x
-4 * -4 = 16
2007-06-28 21:46:39
·
answer #3
·
answered by wael t 1
·
0⤊
0⤋
(2x - 4).(2x - 4)
= 4x² - 8x - 8x + 16
= 4x² - 16x + 16
2007-07-02 17:22:07
·
answer #4
·
answered by Como 7
·
0⤊
0⤋
4x^2 -8x - 8x + 16
4x^2 - 16x + 16
4(x^2 - 4x +4)
4(x - 2)(x - 2)
4(x - 2)^2
2007-06-28 21:34:46
·
answer #5
·
answered by Anonymous
·
1⤊
0⤋
(2x-4)² use fFOIL
(2x-4)(2x-4)
First: 4x²
Outside: -8x
Inside: -8x
Last: 16
Sum: 4x²-16x+16
2007-06-28 22:23:00
·
answer #6
·
answered by yupchagee 7
·
0⤊
0⤋